Microscopic quasiparticle-phonon model and its application - Toivanen, Jussi (1998)
In this work a microscopic three-step model for the excitations of an odd-A nucleus is presented. The model, Microscopic Quasiparticle Phonon Model (MQPM) constructs the excited states of an odd-A nucleus by coupling BCS quasiparticles and eigenmodes (QRPA phonons) of the nearby even-A nucleus together. A detailed derivation of the most complicated parts of the MQPM equations of motion is presented. The reduced matrix elements of charge-changing transition densities, needed in beta-decay calculations, are presented. The MQPM is applied to various nuclei and the resulting state energies and comparative beta-decay half-lives (log ft values) are compared with experiments. The predictive power of the MQPM is discussed.